Optimization on structure and parameters of a collision-pneumatic hybrid rice pollination machine - WANG Yongwei; HE Zhuoliang; CHEN Jun; WANG Jun; ZHANG Lingyue; TANG Yanhai (浙江大学学报. 农业与生命科学版)
To realize pollination mechanization for hybrid rice seed production, a collision-pneumatic hybrid rice pollination machine was designed and manufactured. The airflow velocity in the air hole of pollination tubes with diameter of 50, 55, 60, 65 and 70 mm was simulated by computational fluid dynamics (CFD). The results showed that the average airflow velocity simulated in the air hole of pollination tube with the diameter of 60 mm was similar to the measured value. The field pollination experiments at the average airflow velocity of 9.35, 11.82 and 15.07 m/s were conducted with the spacing between the air hole and collision rope of 50, 100 and 150 mm respectively. The pollen amount received by four line female parents beside male parents was super to that of the artificial pollination and distributed uniformly. The pollen amount distributed on the four line female parents increased with the distance between the air hole and collision rope. However, the pollen amount was not obviously increased when the distance between the air hole and collision rope increased to 100-150 mm, and the average airflow velocity of the air hole increased to 11.82-15.07 m/s. In conclusion, the optimal pollination parameters for the collision-pneumatic hybrid rice pollination machine are obtained when the airflow velocity is 11.82 m/s, and the distance between the air hole and collision rope is 100-150 mm.